Analisis Putusan Hakim terhadap Pelaku Tindak Pidana Pembunuhan Berencana Berdasarkan Putusan Nomor 668/Pid.B/2019/Pn.Jkt.Tim dan Putusan Nomor 1001/Pid.B/2021/Pn.Jkt.Tim - Soni Widianto (Peneliti.net, 2023)
In applying Article 340 of the Criminal Code to the case of premeditated murder based on Decision Number 668/PID.B/2019/PN.Jkt.Tim and Decision Number 1001/Pid.B/2021/PN.Jkt.Tim the Defendants were sentenced, then in accordance with the provisions of Article 222 paragraph (1) in conjunction with Article 197 paragraph (1) letter i of the Criminal Procedure Code, the Defendants are burdened to pay court costs and with due regard to the provisions of Article 340 Jo. Article 56 paragraph (2) of the Criminal Code. Meanwhile, in Decision Number 1001/Pid.B/2021/PN.Jkt.Tim the Defendant was charged with Article 340 of the Criminal Code where the judge was incorrect in the verdict, namely even though he had stated that the Defendant RIDHO IHWANSYAH BIN ROZALI was legally and convincingly proven guilty of committing the crime of